Cutaneous silent period recordings in demyelinating and axonal polyneuropathies. Issue 9 (September 2015) - Lopergolo, Diego; Isak, Baris; Gabriele, Maria; Onesti, Emanuela; Ceccanti, Marco; Capua, Gelsomina; Fionda, Laura; Biasiotta, Antonella; Di Stefano, Giulia; La Cesa, Silvia; Frasca, Vittorio; Inghilleri, Maurizio
Highlights The evaluation of cutaneous silent period (CSP) is a useful method to detect dysfunction of A-delta fibres in patients with axonal polyneuropathy (PNP) as well as demyelinating PNP. The number of axons and conduction properties of A-delta fibres play respectively crucial roles in CSP duration and CSP latencies. CSP parameters do not differ between patients with and without neuropathic pain.